2014
DOI: 10.1021/jf503557t
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the Neonicotinoid Insecticide Acetamiprid via the N-Carbamoylimine Derivate (IM-1-2) Mediated by the Nitrile Hydratase of the Nitrogen-Fixing Bacterium Ensifer meliloti CGMCC 7333

Abstract: The metabolism of the widely used neonicotinoid insecticide acetamiprid (ACE) has been extensively studied in plants, animals, soils, and microbes. However, hydration of the N-cyanoimine group in ACE to the N-carbamoylimine derivate (IM-1-2) by purified microbes, the enzyme responsible for this biotransformation, and further degradation of IM-1-2 have not been studied. The present study used liquid chromatography–mass spectrometry and nuclear magnetic resonance spectroscopy to determine that the nitrogen-fixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…AAP degradation tted rst-order dissipation kinetics (R ¼ 0.99) with a half-life of 182 h. In contrast, AAP was barely degraded in control water without bacterial inoculation. We previously isolated an E. meliloti CGMCC 7333, which could degrade 65.1% of 500 mg L À1 AAP in 96 h with a half-life of 63 h. 16 However, this strain showed weak AAP degradation in surface water samples (data not shown). E. meliloti (formerly Sinorhizobium meliloti) is a symbiotic nitrogen-xing bacterium, and is usually limited by application of microbes-plants combined remediation.…”
Section: Lc-ms Analysis Indicated That the Metabolite Displayed A Promentioning
confidence: 99%
“…AAP degradation tted rst-order dissipation kinetics (R ¼ 0.99) with a half-life of 182 h. In contrast, AAP was barely degraded in control water without bacterial inoculation. We previously isolated an E. meliloti CGMCC 7333, which could degrade 65.1% of 500 mg L À1 AAP in 96 h with a half-life of 63 h. 16 However, this strain showed weak AAP degradation in surface water samples (data not shown). E. meliloti (formerly Sinorhizobium meliloti) is a symbiotic nitrogen-xing bacterium, and is usually limited by application of microbes-plants combined remediation.…”
Section: Lc-ms Analysis Indicated That the Metabolite Displayed A Promentioning
confidence: 99%
“…Microbiological degradation plays key roles in the dissipation of acetamiprid from the environment, as well as in the detoxification of acetamiprid. Many prokaryotic and eukaryotic microorganisms have been reported to be capable of degrading acetamiprid (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Strain D-2, previously isolated in our laboratory, could degrade over 99% of 0.22 mM acetamiprid in 3 days, showing that it possesses a very high degradation capability.…”
Section: Discussionmentioning
confidence: 86%
“…The environmental fate of acetamiprid has attracted considerable attention, and microbial degradation is the key means for the dissipation of acetamiprid from the environment (15,16). In recent years, several microbial strains capable of degrading acetamiprid have been isolated, and the catabolic pathways of acetamiprid have been extensively studied (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Four catabolic pathways of acetamiprid are illustrated in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolysis and photolysis of acetamiprid should also be minor in the biochar‐amended sand because the experimental conditions are similar. A number of studies (Liu et al, 2011; Wang et al, 2013a, 2013b; Yang et al, 2013; Zhou et al, 2014b) showed that the primary degradation pathway for the acetamiprid is aerobic soil metabolism. The microorganisms in the biochar likely induced biodegradation of acetamiprid.…”
Section: Resultsmentioning
confidence: 99%